Allosteric inhibition of SARS-CoV-2 3CL protease by colloidal bismuth subcitrate. Issue 42 (11th October 2021) - Tao, Xuan; Zhang, Lu; Du, Liubing; Liao, Ruyan; Cai, Huiling; Lu, Kai; Zhao, Zhennan; Xie, Yanxuan; Wang, Pei-Hui; Pan, Ji-An; Zhang, Yuebin; Li, Guohui; et al.
Abstract : Colloidal bismuth subcitrate (CBS) is an allosteric inhibitor of 3-chymotrypsin-like protease (3CLpro) in SARS-CoV-2. CBS binding causes dimeric 3CLpro dissociation and proteolytic dysfunction, leading to the suppression of SARS-CoV-2 replication. Abstract : The SARS-CoV-2 3-chymotrypsin-like protease (3CLpro or Mpro) is a key cysteine protease for viral replication and transcription, making it an attractive target for antiviral therapies to combat the COVID-19 disease. Here, we demonstrate that bismuth drug colloidal bismuth subcitrate (CBS) is a potent inhibitor for 3CLpro in vitro and in cellulo . Rather than targeting the cysteine residue at the catalytic site, CBS binds to an allosteric site and results in dissociation of the 3CLpro dimer and proteolytic dysfunction. Our work provides direct evidence that CBS is an allosteric inhibitor of SARS-CoV-2 3CLpro.